Representasi Poligami Dalam Film “Bismillah Kunikahi Suamimu” - Ali Syahputra (QISTHOSIA : Jurnal Syariah dan Hukum, 2024)
This paper examines the practice of polygamy represented in the film Bismillah Kunikahi Suamimu by Vyntiana Itari. This paper explores the phenomenon of polygamy in a film that raises the question of how polygamy is represented in the film Bismillah Kunikahi Suamimu. The issue of polygamy in a film is very interesting to study to see if a film can provide education to the public. Through this film, people will easily gain knowledge, even though they are just watching, but without realizing they will gain knowledge. This research uses a qualitative approach by using Sara Mills' discourse analysis, the researcher's subjective interpretation is based on the representation theory developed by Stuart Hall. This paper focuses on the perspective of feminism and analyzes the position of the subject-object and the audience in representing polygamy in the film "Bismillah Kunikahi Suamimu". In this paper, it is found that the movie "Bismillah Kunikahi Suamimu" depicts polygamy from the perspective of women who are empirically the objects in the practice of polygamy. So that it provides more space to provide definitions related to polygamy experienced by women. The results of this study show that in filmmaking, the director is more likely to take the story from a woman's point of view so that the audience will see events from a woman's perspective. The conflict found in the movie "Bismillah Kunikahi Suamimu" is the inner war of women and the unwillingness of parents when their children are polygamous.